Cypress Weevil, Eudociminus mannerheimii (Boheman) (Coleoptera: Curculionidae) - Albert E. Mayfield, III (EDIS, 2019)
The cypress weevil, Eudociminus mannerheimii (Boheman), is a native insect that breeds primarily in scarred, weakened, or fallen bald cypress (Taxodium distichum [L.] L.C. Rich) and pond cypress (T. ascendens Brongn.). In Florida, adult feeding has caused limited wounding and girdling of pond cypress stump sprouts and planted seedlings. Small diameter bald cypress nursery stock has also been damaged by larvae tunneling through the main stem and root collar. Apart from entries in species checklists and catalogs, published information about the cypress weevil is extremely limited (Hopkins 1904, Blatchley and Leng 1916, Baker and Bambara 1999).